Implementation of Remission For Female Prisoner as One of The Rights in The Correction System - Oksidelfa Yanto; Rachmayanthy Rachmayanthy; Djoni Satriana (Jurnal IUS Kajian Hukum dan Keadilan, 2019)
The purpose of this study was to find out about the implementation of remission of female prisoners in the Class II A Tangerang Women's Penitentiary and also to find out the obstacles to the implementation of remission against female prisoners in the Penitentiary. The method used in this study is normative and empirical legal research methods by collecting secondary data and primary data related to research problems. The results of the study indicate that remission is the right of prisoners to get a criminal reduction if during good coaching. Remission is the right of the prisoner if the person in question carries out acts such as doing services to the state and taking actions that are beneficial to the state or humanity, as well as committing acts that help the activities of the prison. There are several factors inhibiting remission in the Class II A Tangerang Women's Penitentiary, namely the difficulty of female inmates meeting the special requirements for the implementation of remission, which is paying fines and replacement money in accordance with court decisions.